2020
DOI: 10.1111/papr.12878
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Combination Technique: Three Points of Epiduroscopic Laser Neural Decompression and Percutaneous Laser Disc Decompression With the Ho:YAG Laser in an MSU Classification 3AB Herniated Disc

Abstract: Aim The aim of this study was to examine the effects of simultaneous epiduroscopic laser neural disc decompression (ELND) and percutaneous laser disc decompression (PLDD) applications using a holmium:yttrium‐aluminum‐garnet (Ho:YAG) laser in Michigan State University (MSU) classification 3AB herniated discs on VAS and Oswestry Disability Index (ODI) scores. Methods In this prospective observational study, ELND and PLDD procedures performed between January 2016 and December 2017 were examined. Preoperative, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A herniation size can be classified as 1‐2‐3. Several clinical studies have confirmed that in regard to selecting appropriate LDH patients who urgently require surgery, the MSU classification is more consistent with that of surgeons 17,18 . Patients with size‐2 or size‐3 lesions may account for a higher proportion of satisfactory surgical outcomes when using the MSU classification to guide surgical options 16 .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…A herniation size can be classified as 1‐2‐3. Several clinical studies have confirmed that in regard to selecting appropriate LDH patients who urgently require surgery, the MSU classification is more consistent with that of surgeons 17,18 . Patients with size‐2 or size‐3 lesions may account for a higher proportion of satisfactory surgical outcomes when using the MSU classification to guide surgical options 16 .…”
Section: Discussionmentioning
confidence: 86%
“…Several clinical studies have confirmed that in regard to selecting appropriate LDH patients who urgently require surgery, the MSU classification is more consistent with that of surgeons. 17 , 18 Patients with size‐2 or size‐3 lesions may account for a higher proportion of satisfactory surgical outcomes when using the MSU classification to guide surgical options. 16 To our knowledge, this is the first LDH diagnostic criterion closely linked with severity evaluation and corresponding clinical decision‐making.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 7 ) suggest that patients with grade 1 should be excluded from surgical consideration, and patients with grade 2 or grade 3 should be considered for performing micro discectomies. This classification system is currently widely used in the clinical setting ( 29 , 30 ). In addition, the classification system of LCCS, a valuable method for clinicians and radiologists to use in clinical practice, is defined by the degree of separation of the cauda equina related to the severity of the clinical signs ( 9 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though low back and radicular pain may usually be managed with conservative approaches, about 20% of patients develop chronic pain [28]. Minimally invasive procedures for treating low back and radicular pain have grown in popularity [29 ▪ ].…”
Section: Chronic Low Back Painmentioning
confidence: 99%